Chapter 18. Therapeutic Drug Monitoring (Evidence-Based Pharmacotherapy in Clinical Practice, 2025)
AuthorDr. Usha Rani EAssociate Professor, Department of Pharmaceutics, Koringa College of Pharmacy, Korangi, Andhra Pradesh, IndiaAbstractTherapeutic drug monitoring protocols consist of pharmacokinetic principles for optimal drug dosing and concentration assessment. Pharmacokinetic analysis utilizes patient-specific parameters including age, organ function, and genetic factors to guide initial dosing strategies. Monitoring parameters selection considers drug-specific characteristics, therapeutic ranges, and clinical response indicators. Results interpretation incorporates multiple factors including sampling timing, drug interactions, and patient-specific variables affecting drug disposition. Dosing adjustments follow systematic protocols based on measured concentrations, clinical response, and adverse effects. Clinical applications encompass multiple drug classes requiring concentration monitoring including anticonvulsants, aminoglycosides, and immunosuppressants. Implementation strategies include standardized sampling protocols, interpretation guidelines, and documentation systems. Monitoring programs incorporate regular assessment of clinical outcomes, adverse effects, and cost-effectiveness measuresKeywords: Drug monitoring, Pharmacokinetics, Concentration measurement, Dose adjustment, Clinical interpretationVIEW PDF